A Case of Combined Hepatocellular‐Cholangiocarcinoma Diagnosis and Treatment With Literature Review - Xuliang Chen; Hengkai Zhu; Liyan Tao; Shusen Zheng; Hua Guo (Clinical Case Reports)
ABSTRACT This report presents a rare case of a 43‐year‐old man with unresectable combined hepatocellular‐cholangiocarcinoma who, after undergoing transarterial chemoembolization, systemic chemotherapy, and stereotactic body radiation therapy, accepted curative resection and obtained an overall survival of 25 months to date. The case highlights the need for adaptable treatment regimens due to the tumor's components and underscores the importance of surgery for long‐term success.